Galactofuranose side chains in galactomannans from Penicillium spp. modulate galectin-8-mediated bioactivity. (15th September 2022) - Zhang, Siying; Lin, Zhiying; Wang, Dongmei; Xu, Xuejiao; Song, Chengcheng; Sun, Lin; Mayo, Kevin H.; Zhao, Zihan; Zhou, Yifa
Abstract: Polysaccharides from fungi have many bioactivities. Previous studies showed that galactomannans from Penicillium oxalicum antagonize galectin-8-mediated activity. Here, two intracellular and two extracellular galactomannans were purified and their structures were comparatively characterized by NMR, partial acid hydrolysis and methylation. All four of them were identified to be galactomannans with similar mannan backbones having 1, 2-/1, 6-linkages (~3:1) and various amounts of galactofuranan side chains. The interaction of those polysaccharides with galectin-8 was assessed by hemagglutination and biolayer interferometry. These results show that side chains are important for the interaction, and the more the side chains, the stronger the interaction. But the side chains alone did not show act on galectin-8, which indicated that the cooperation between backbone and side chains is another necessary factor for this interaction. Our findings provide important information about structure-activity relationships and the galactofuranose-containing galactomannans might be as potential therapeutic of galectin-8 related diseases. Graphical abstract: Unlabelled Image